2021
DOI: 10.1021/acs.jafc.1c03427
|View full text |Cite
|
Sign up to set email alerts
|

Weak Binding of Epigallocatechin to α-Lactalbumin Greatly Improves Its Stability and Uptake by Caco-2 Cells

Abstract: Improving the stability and bioavailability of catechins is of great importance. Epigallocatechin (EGC), the major catechin in green tea, is a potent antioxidant with numerous attributed health benefits. However, the low permeability and stability limit its enrichment in the diet for preventive medicine. In this study, we explored the interaction of EGC and α-lactalbumin by spectroscopic, thermodynamic, and crystallographic methods. The isothermal titration calorimetry experiments elucidated that αlactalbumin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…These results indicated that HPP could promote the transformation of the α-helix of α-La to random coils, which represented the presence of unfolding conformation and might further induce the volume shrinkage of protein under pressure [ 22 ]. Due to its certain flexibility, the random coil structures are the main parts of the binding sites responsible for the recognition of small-molecule ligands [ 28 , 33 ], and in a few cases, the a-helix plays an important role [ 34 ]. For the thermally processed samples, the α-helix content decreased as the processing temperature increased to 80 °C but decreased sharply at 60 °C at all pH conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that HPP could promote the transformation of the α-helix of α-La to random coils, which represented the presence of unfolding conformation and might further induce the volume shrinkage of protein under pressure [ 22 ]. Due to its certain flexibility, the random coil structures are the main parts of the binding sites responsible for the recognition of small-molecule ligands [ 28 , 33 ], and in a few cases, the a-helix plays an important role [ 34 ]. For the thermally processed samples, the α-helix content decreased as the processing temperature increased to 80 °C but decreased sharply at 60 °C at all pH conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the percentage of peak II intensity was reduced under pressure, and that of peak III intensity increased obviously instead. The peak at around 229 nm indicates that the protein mainly exists in the form of large polymers in solution, while the appearance of the new peak III demonstrates that the HPP might induce the formation of a compact conformational subset or small aggregates of the α-La monomer [ 34 ]. At pH 6.0, the intensity of peak I decreased under a pressure of 100 MPa but increased at 300 MPa and 500 MPa; similar phenomena also occurred in samples at pH values of 7.4 and 8.0.…”
Section: Resultsmentioning
confidence: 99%
“…The cell culture and cell viability assay was carried out with cell counting kit-8 as reported. 18 Caco-2 cell cultures were obtained from American Type Culture Collection, Rockville, MD, USA. The cells were incubated in a humidified incubator of air/CO 2 (95 : 5) at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the initial rate of iron release, the kinetic curve was fitted using a third-order equation based on the previous report: Y = A 0 + A 1 t + A 2 t 2 + A 3 t 3 and dY/dt = A 1 + 2A 2 t + 3A 3 t 2 (at t = 0, (dY/dt) 0 = v 0 ). (5) In this equation, t stands for time, and Y is the concentration of [Fe(ferrozine) 3 ] 2+ at t minutes [47]. As illustrated in Figure 6A, when PZ: FA was at 1:22, 1:44, and 1:66, the initial release rate of iron decreased to 24.72, 39.96, and 93.11 nM/min, respectively, compared to without PZ addition (99.86 nM/min).…”
Section: Inhibition Of Iron Release Through Pz-fa Interactionsmentioning
confidence: 99%
“…Interestingly, protein-small molecule interactions occur commonly in foodstuffs as well, particularly protein-polyphenol interactions. Such interactions could improve protein properties such as thermal stability, surface hydrophobicity, and structural stabilization, while protecting small molecules against light-, thermal-, and pH-induced damage [3][4][5].…”
Section: Introductionmentioning
confidence: 99%